Testing for Profitability and Contestability in Banking - Franz R. Hahn (Austrian Institute of Economic Research (WIFO), 2005)
The paper investigates the determinants of banking profitability and banking market conditions in Austria. We conduct a panel econometric analysis which allows for testing the hypotheses which have become the most prominent in the literature on bank profitability: the structure-conduct-performance hypothesis, the efficient-structure hypothesis and the relative-market-power hypothesis. Further, we test whether Austrian banking markets are, on average, contestable. A newly compiled dataset covering more than 700 Austrian banks ranging over the period from 1995 to 2002 is used to carry out these econometric analyses. The empirical findings support the view that the Austrian banks do exert, on average, some local market power. However, the gains in terms of excess profits are rather minor due to low deterrence powers of the incumbent banks.
Keywords: G21; L13; L25; L44; 330; banking performance; banking profitability; banking market structure; panel econometrics; Bank; Finanzmarkt; Rentabilität; Panel; Österreich